Insurance Enterprise Financial Security: Evaluation and Providing Directions. (Economics and region, 2019)
The theoretical substantiation of concept explanation «insurer’s financial security» was done, which allowed common elements distinguishing and differences in the treatment of scientists. It is proposed to treat financial security as an insurance company's ability, as well as a condition that further requires its ability to analyze, evaluate, and providing directions determination. The factors influencing the insurance enterprise financial security and the set of measures for its providing are revealed.
Keywords: financial security; insurance enterprise (company); fluidity (liquidity); credit standing; financial accountability; economic activity